Turismo responsável na Serra Grande - Cantá/RR: uma contribuição da percepção dos stakeholders na construção de uma proposta de gestão compartilhada - Alves, Leidiane do Nascimento (2023)
The tourist activity started to use natural environments for the practice of leisure and adventures. However, using nature for the practice of tourism is somewhat worrying, and it is necessary to be careful and concerned about the impacts that this practice can bring to the environment and the surrounding community. In this context, responsible tourism emerges, bringing answers to the challenges of sustainability. However, for responsible tourism to become effective, it is necessary to adopt a shared management approach, involving the participation of all stakeholders. This study sought to identify the challenges for building a shared management project for responsible tourism in Serra Grande – Cantá/RR, from the perspective of stakeholders. To achieve this objective, the following specific objectives are: Investigate the perception of visitors regarding the tourist experience experienced in Serra Grande; outline a situational overview of tourist activity in Serra Grande, based on demand and tourist supply; analyze the role and involvement of stakeholders in the process of planning and managing tourism; and to evaluate the main actions, difficulties and opportunities of planning and management to analyze the performance and involvement of the stakeholders regarding the process of planning and management of tourism; and evaluate the main actions, difficulties and opportunities of planning and management with a view to the realization of tourism. Located in the municipality of Cantá and has trails, waterfalls, panoramic views for nature lovers.The participants in this survey were the following stakeholders: 90 visitors, 85 residents of Vila Serra Grande 1 and Vicinal Rio Branco, 10 businessmen from tourism agencies in Boa Vista and Cantá; 10 conductors from the Rio Branco road and the secretary of the Municipal Secretary of Culture, Leisure, Tourism and Sports. Questionnaires were applied to the community in person and to tourists online through Googleforms. The interviews (semi-structured) were conducted with the businessmen, the drivers and the secretary in person, and a cell phone was used to record the information provided by the participants. Data collections were carried out during the month of April and May 2023. Quantitative data were systematized and organized using Excel software, R studio for the construction of graphs and qualitative data were analyzed using Bardin's content analysis method. In the present study, dissatisfaction with the local infrastructure on the part of the stakeholders was identified, as well as the lack of safety on the trails. It was also evident that the participation of stakeholders in the management of tourism in the locality does not occur, as well as the absence of action by the public power. It was also observed that stakeholders do not play an active role in the local tourism management process and act in isolation. And as for the action of the public power, it is still incipient, leaving something to be desired. However, there is a great challenge in carrying out shared management, given that stakeholders are disconnected and there is no synergy between their actions.